2017
DOI: 10.1016/j.jiph.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection among 71,435 women in Jiangxi Province, China

Abstract: Cervical cancer is the third most common cancer in women worldwide. Human papillomavirus (HPV) has been identified as an etiological factor for cervical cancer. Data on the prevalence and subtype distribution of HPV infection in Jiangxi Province are incomplete. In this study, we investigated HPV subtype distribution and prevalence in Jiangxi Province between August 1, 2010, and December 31, 2015. A total of 71,435 individuals ranging in age from 16 to 77 years were recruited. Cervicovaginal swabs were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
5

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 23 publications
7
40
5
Order By: Relevance
“…In addition, for hr‐HPV genotypes, the 5 common subtypes in decreasing order were HPV 16, 52, 58, 33, and 18. The results of this study are similar to other literature . While other researches suggested that the most frequent HPV genotypes of HSIL were HPV 16, 58, and 18; HPV 16 and 52; and HPV 53, 58, and 52 in Sichuan, Shanxi, and Korea, respectively .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, for hr‐HPV genotypes, the 5 common subtypes in decreasing order were HPV 16, 52, 58, 33, and 18. The results of this study are similar to other literature . While other researches suggested that the most frequent HPV genotypes of HSIL were HPV 16, 58, and 18; HPV 16 and 52; and HPV 53, 58, and 52 in Sichuan, Shanxi, and Korea, respectively .…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies from different areas in China proved that the overall HPV infection rates were 22.4%, 38.3%, 17.6%, and 24.1%, respectively. However, our research suggested that the overall prevalence of HPV infection was 74.0% among the HSIL and ICC women.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…All above findings of our study indicated that in addition to HPV16, 18, 6, and 11, HPV vaccines in Guangdong should also include HPV31, 33, 39, 52, 53, 58, 68, and CP8304 genotypes. In addition, HPV screening programs in China aim to detect only HPV6, 11, 16, and 18 . When considering the HPV distribution in Guangdong from our study, HPV screening systems should focus on HPV52, 58, 53, and 39 equally to HPV16 and 18.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that nonvaccine HPV genotypes may displace HPV vaccine genotypes as causal agents of cervical cancer and precancerous lesions in vaccinated populations . In addition, HPV screening programs in China aim to detect only HPV6, 11, 16, and 18 . Thus, regional data on the type‐specific HPV prevalence and distribution in women of different populations are essential.…”
Section: Introductionmentioning
confidence: 99%